Microarray analysis of preterm preeclampsia - Liu, Huina; Yu, Junjie; Yuan, Wenjing; Shi, Huirong; Guan, Wenli (Cellular and Molecular Biology, 2020)
Premature preeclampsia is the second cause of maternal mortalities around the world. To investigate its potential driving mechanism(s), we constructed a multi-regulatory-mediated preeclampsia dysfunction module. Through combining differential expression analysis, co-expression analysis, and enrichment analysis, we obtained 23 sets of preeclampsia expression disorder modules in the disease, which involve the modular aggregations of 3016 genes. The modules were subjected to be analyzed for GO and KEGG paths for enrichment analysis. Based on these pivotal regulators, it is possible to manipulate the essential parts of the modular subnetwork and study their cooperative acts to mediate the driving mechanism of the preeclampsia. Simultaneously, they mainly cause the onset of the disease through the regulation of the apoptotic signaling pathway, down-regulation of an inflammatory response and retinol metabolism. This may present a potential driving mechanism for the disease. The predictor analysis of the regulators showed a series of non-coding RNAs that have potentially significant regulatory effects on the disease, including miR-182-5p, miR-200b-3p, miR-23a-3p, miR -429, miR-590-3p, and transcription factors. These pivotal regulators might mediate the potential driving processes. Based on a comprehensive multivariate analysis, we found a possible driving mechanism in which significant pivotal regulators were used as distinct functional segments in the preterm preeclampsia-driven process.